Replenishment system using inventory models with continuous review and quantitative forecasting to reduce stock-outs in a commercial company - Malca-Ramirez, Carlos (2020)
In recent years, stock-outs significantly affects commercial enterprises with deficit equivalent to a large percentage of the total sales, due to its impact on current and future demand, regardless of their financial success. Carried out a qualitative and quantitative analysis of the current situation to identify the problem. In addition, the root causes were identified with the help of quality tools such as Pareto chart and Ishikawa and a questionnaire based on the SCOR model and management indicators. In this way why it is proposed a replenishment system applying models of inventories with continuous review and quantitative forecasts. The proposal consists of five phases: (i) identify the key products; (ii) Do quantitative forecasting; (iii) Determine inventory levels. (iv) Establish the new flow of information; (v) Establish new policies and procedures. We evaluate the models of inventories and forecasts through the program arrobaRisk.